HEPATOPROTECTIVE AND NEPHROPROTECTIVE EFFECTS OF TOFACITINIB AND ASPIRIN AS ANTI-INFLAMMATORY DRUGS TARGETING JAK-STAT AND NF-κB SIGNALING PATHWAYS IN TYPE 2 DIABETES-INDUCED RATS. - BAKO, HAUWAU YAKUBU; Mohammed Auwal Ibrahim; Sani Ibrahim (FUDMA Journal of Sciences, 2025)
Chronic inflammation contributes to hepatic and renal complications in type 2 diabetes, largely through dysregulation of the JAK–STAT and NF-κB signaling pathways. This study evaluated the hepatoprotective and nephroprotective effects of tofacitinib (JAK–STAT inhibitor) and aspirin (NF-κB inhibitor) in streptozotocin-induced type 2 diabetic rats. Type 2 diabetes was induced using streptozotocin. Diabetic rats were treated orally with tofacitinib (10 or 20 mg/kg), aspirin (100 or 200 mg/kg), or combination therapy for 9 weeks. Serum ALT, AST, creatinine, and urea levels were quantified, and liver and kidney tissues were examined histologically. Statistical significance was set at P < 0.05. Diabetic controls showed substantial increases in ALT (74.56 ± 4.71 U/L), AST (181.30 ± 16.91 U/L), creatinine (45.33 ± 2.17 mg/dL), and urea (198.25 ± 6.49 mg/dL). Tofacitinib significantly reduced ALT to 32.32 ± 4.22 and 33.07 ± 4.06 U/L, AST to 79.80 ± 7.38 and 74.67 ± 6.37 U/L, creatinine to 17.25 ± 1.26 and 10.38 ± 1.02 mg/dL, and urea to 91.07 ± 9.48 and 61.36 ± 5.99 mg/dL at 10 and 20 mg/kg, respectively (P < 0.05). Aspirin at 100 mg/kg produced comparable improvements, while 200 mg/kg aspirin and combination regimens failed to significantly improve biomarkers (P > 0.05). Histopathology confirmed reduced hepatocyte degeneration and glomerular injury in effective treatment groups. In conclusion, tofacitinib and low-dose aspirin independently confer significant hepatoprotective and nephroprotective effects in type 2 diabetic rats, whereas combined therapy provides no added benefit.
Keywords: Complications; Hepatotoxicity; Inflammation; Nephrotoxicity; Type 2 Diabetes